EFFECT OF COW DUNG AND COW URINE COMBINATION FOR THE CONTROL OF COWPEA FIELD PESTS IN BAUCHI STATE, NIGERIA - Isah, K.A.; Aliyu, M.; Sabo, U.M.; Shuaibu, Y.M.; Abdu, A.I. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
Field trial was conducted during the rainy season of 2024at Abubakar Tafawa Balewa University, Teaching and Research Farm Bauchi, to investigate the effect of cow dung and cow urine combination for the control of cowpea field pests. The treatments consisted of three (3) rates of cow dung + cow urine (2.5, 5.0 and 7.5 l/ha), 2%Acetamiprid+1.5%Lamdacyhalothrine EC (1 l/ha) and a control. These were combined to give 5 treatments, laid out in a randomized complete block design and replicated three times. The result revealed a significant difference (P≤0.01) among the treatments on number of aphids per plant, proportion (%) of plants infested by aphids, number of maruca larva per flower, proportion of flowers infested by larva, number of damaged pods, number of clavigralla per plants, number and percentage of shriveled pods. The result also showed that cowpea treated with either cow dung+cow urine (7.5 l/ha) or 2%Acetamiprid+1.5%Lamdacyhalothrine had the lowest number of aphids, maruca and clavigralla infestation. Control plot on the other hand, had the highest proportion of plants infested by aphids, maruca as well as clavigralla. Yield and yield components on the other hand, cowpea treated with either cow dung+cow urine (7.5L/ha) or 2%Acetamiprid+1.5%Lamdacyhalothrine had the highest number of seeds per pod and highest grain yield (913.23 kg/ha and 927.10 kg/ha). Cow dung and cow urine combination had significantly impacted cowpea yield and insect pest infestation, therefore, it is recommended to treat cowpea with 7.5 l/ha cow dung and cow urine combination for the control of cowpea field pests and higher yield.